We'll take it from here: Veterans Affairs OPAT management of home IV therapy initiated at community hospitals - Allison R. Tiemann; Jessica M. Guastadisegni; Marcus A. Kouma; Kevin C. Kelly; Reuben J. Arasaratnam; Donald F. Storey (Cambridge University Press, 2023)
An outpatient parenteral antimicrobial therapy team from a Veterans Affairs facility managed patients discharged from their own facility and neighboring community hospitals. There were no significant differences in adverse outcomes between the groups, but a majority of regimens were modified from those initially proposed by community providers.